Evaluation of portable potentiostats for electrochemical measurements: Voltammetry and Impedance spectroscopy - Abdul Ghani, Muhammad Afiq; Nordin, Anis Nurashikin; Ab Rahim, Rosminazuin; Gunawan, Teddy Surya; Mohd Zain, Zainiharyati (IEEE, 2022)
A potentiostat is needed to perform electrochemical measurements but lab-grade potentiostats are lacking portability. Portable potentiostats, μStat-i 400 DropSens, and Pico Development Kit are evaluated against labgrade potentiostat, Autolab PGSTAT302N. Evaluations are being done with voltammetry and impedance spectroscopy. A comparison of cyclic voltammetry and impedance spectroscopy had been done with a 10mM ferrocyanide solution. Slight differences were detected when the test was run on the screen-printed carbon electrode, but the differences are very small when tested with the gold electrode. Then, the evaluation continued with probe DNA, target sequences, and 10mM ferrocyanide solution with differential pulse voltammetry. The evaluation is being done using the screen-printed gold electrode. The result showed similar results across three potentiostats. The slight discrepancies in the evaluation are happening due to the limitation of the portable potentiostat. Differences in the technologies of different companies could result in discrepancies. Through this study, portable potentiostats have the potentials to compete with lab-grade potentiostats.